Introduction to fish nutrition - Rauthan JVS (New Delhi MEDTECH, 2021)
The comprehensive text of this book has been designed to cater the academic needs of under-graduate, post-graduate students and researchers of fisheries science. The book covers the core module syllabus on fisheries science (fish nutrition) prepared by various universities. It is a comprehensive treatise on nutrient requirements in major species of fish. Hence this book is of wider utility for all those interested to know about fish nutrition. The book covers wide array of topics spread over 16 chapters including Bioenergetics, Nutritional Physiology, Formulation and Manufacture of Diet, Intermediary Metabolism, Nutritional Pathology, Diet and Fish Husbandry, Adventitious Toxins, Nutrition Flow and Retention, Special Feeds, and many more. It also highlights basic physiology and biochemistry for the major species used worldwide in aquaculture.
Keywords: Food Technology